A Calpain-like multigene family in trypanosoma brucei - Olego-Fernandez, S (2010)
Trypanosomatid parasites are unicellular eukaryotes characterised by the presence of a subpellicular array of microtubules, a single flagellum, and a kinetoplast (containing the condensed mitochondrial DNA). The majority of trypanosomatid species undergo complex life-cycles, alternating between a mammalian host and an insect vector. Progression through this life-cycle requires the differentiation of trypanosomatids into distinct, niche adapted developmental forms. Differentiation into each life-cycle stage involves important biochemical and morphological changes, including the remodelling of the subpellicular cytoskeleton that defines cell shape. In higher eukaryotes, proteins from the calpain superfamily are involved in developmentally- and environmentally-regulated remodelling of the cytoskeleton and the dynamic organisation of signal transduction cascades. Interestingly, trypanosomatids contain unusually large families of calpain-related proteins, but there is little knowledge about the functional roles of these molecules during the life-cycle of trypanosomatid parasites. In this thesis, I present the results of the bioinformatic analysis of calpain-like proteins in three trypanosomatid parasites, Trypanosoma brucei, Leishmania major and Leishmania infantum. From this analysis, I selected several calpain-related proteins tor RNAi functional analysis, on the bases of their domain composition and conservation across different species. The detailed analysis of the resulting RNAi phenotypes revealed the essential function of some calpain-like proteins for the correct morphogenesis of specific developmental forms of T. brucei, shedding some light on the mechanisms that regulate this parasite differentiation and cytoskeletal remodelling, and providing new putative therapeutic targets for African sleeping sickness.